Enhancing Organizational Commitment through Organizational Climate Strengthening, Self Efficacy and Job Satisfaction Program (An Empirical Study of Permanent Employees in Multifinance Industry In Jakarta) - Joko Ariawan; Didik Notosudjonor; Widodo Sunaryo (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to formulate effective strategies for enhancing employee organizational commitment through organizational climate, self-efficacy, and job satisfaction. The population consisted of 1,294 permanent staff-level employees working in multifinance companies in Jakarta. A proportional random sampling technique was applied using Slovin’s formula with a 5% margin of error, resulting in a sample of 248 respondents. A mixed-methods approach was employed, combining quantitative analysis using path analysis with qualitative analysis through expert judgment to develop strategic recommendations. The quantitative findings indicate that organizational climate, self-efficacy, and job satisfaction have direct, positive, and significant effects on organizational commitment. In addition, organizational climate and self-efficacy exert indirect positive effects on organizational commitment through job satisfaction as a mediating variable, although the direct effects are stronger than the indirect ones. Qualitative findings support the quantitative results, emphasizing the role of leadership support, employee capability development, and career growth opportunities. This study provides practical recommendations for companies to design effective human resource interventions aimed at strengthening organizational commitment and enhancing workforce sustainability within the multifinance industry.